Effect of fluid contamination on the removal torque of abutment screws - Tuba Toprak; Göknil Alkan Demetoğlu (BMC Oral Health)
Abstract Background Screw loosening is one of the most common mechanical complications of implant-supported restorations. The purpose of this study was to evaluate the effects of contamination with different liquids on the removal torque values (RTVs) in the implant‒abutment connection. Methods A total of 66 DTI implants (6 groups, 11 implants in each group) were used. The screw holes of 55 implants were contaminated with either blood from a 29-year-old female donor (BG), saliva (SG), a blood and saliva mixture (BS), blood and Ankaferd Blood Stopper mixture (BA), topical anesthetic (TA), and the remaining noncontaminated screws served as a control group (NC). Afterwards, the abutment screws were tightened to the implants via a digital torque meter (DID-4 A) with a torque of 20 Ncm. RTVs were recorded after thermocycling. The data obtained from the study were statistically evaluated via the Shapiro‒Wilk test, the Levene test, one-way analysis of variance and the Bonferroni correction. Results When the average removal torque of the groups were examined, the group with the highest average value was the control group. All contaminating agents in clinical conditions caused screw loosening. Conclusion Clinicians should consider that RTVs ​​may be affected by contamination of the implant abutment screw hole with blood, saliva, hemostatic agent or local anesthetic solution.